BISMUTH RAMDOHRITE, A NEW SULFOSALT - Borodayev Y.S.; Mozgova N.N.; Nenasheva S.N.; Kuz'mina O.V.; Yefimov A.V.; Sivtsov A.V. (My University, 1989)
While studying ore minerals of the Alyaskitovoye ['Alaskite'] tin-tungsten deposit in Yakutia, we found Bi-ramdohrite (≤ 22.5 weight percent bismuth). Among all hitherto known ramdohrites, it is closest in composition (sum Sb and Bi) to Alfeld's ramdohrite and differs markedly from bismuth andorites recently studied by us under the same conditions (≤ 30 weight percent Bi). This mineral occurs as clusters of equidimensional or myrmekitic grains (no larger than 0.3 mm) in quartz or in microcrystalline galena-matildite-aramayoite exsolution textures, sometimes with laths of bismuth owyheeite. In the latter, myrmekitic intergrowths of Bi-ramdohrite are sometimes distributed fairly uniformly in the galena-matildite-aramayoite lattice and, together with the latter, evidently form an earlier coarse-grained exsolution texture. From our work, we can draw conclusions concerning not only ramdohrite, but also the whole andorite series.